Penegakan Disiplin Perangkat Sekretariat Desa di Kecamatan Kampar Kiri Hulu Kabupaten Kampar - Busrianto, Busrianto; yalid, yalid (Jurnal Panorama Hukum, 2020)
The formulation of the problem in this study are 3 (three). First, how is the discipline enforcement of the Village Secretariat Apparatus in Kampar Kiri Hulu District, Kampar Regency? Second, what are the obstacles in enforcing the discipline of the Village Secretariat in Kampar Kiri Hulu District, Kampar Regency? Third, how are the efforts to enforce the discipline of the Village Secretariat Apparatus in Kampar Kiri Hulu District, Kampar Regency? In line with the formulation of the problem, the objectives of this study are 3 (three). First, to explain the discipline enforcement of the Village Secretariat Apparatus in Kampar Kiri Hulu District, Kampar Regency. Second, to explain the obstacles in enforcing the discipline of the Village Secretariat Apparatus in Kampar Kiri Hulu District, Kampar Regency. Third, to explain the efforts to enforce the discipline of the Village Secretariat Apparatus in Kampar Kiri Hulu District, Kampar Regency. This type of research is sociological legal research, according to the type, the approach is empirical. The results of this research can be explained that the authority of the Village Head can dismiss the Village Secretariat Apparatus as guided by the Kampar District No. 12 of 2017. Obstacles in disciplinary enforcement of the Village Secretariat Apparatus in Kampar Kiri Hulu Subdistrict, Kampar Regency are due to the long distance, transportation and communication facilities because not all villages in Kampar Kiri Hulu have telephone networks, so to communicate with the Village Secretariat Apparatus must find and speak directly. Efforts to enforce the discipline of the Village Secretariat Apparatus in Kampar Kiri Hulu District, Kampar Regency require efforts in the form of legal discipline standards according to the applicable law. Regarding this matter, only part of the services of the Village Secretariat Apparatus in Kampar Kiri Hulu District already have the said standard. This is obtained based on the facts of interviews with related respondents.